Meconium Peritonitis, Intestinal Atresia Combined With Biliary Atresia: A Case Report - Han, Yijiang; Hu, Shuqi; Chen, Baohai; Huang, Shoujiang; Qin, Qi; Tou, Jinfa (Frontiers in Pediatrics, 2022)
Meconium peritonitis (MP) combined with intestinal atresia (IA) is a rare neonatal condition, and it is even rarer in combination with biliary atresia (BA). We describe a case of an infant who developed short bowel syndrome after partial intestinal resection due to MP and IA, along with a Santullienterostomy. During continuous enteral and parenteral nutrition, the stool color became paler. BA was identified by elevated direct bilirubin (DBIL), gamma-glutamyltransferase (GGT), serum matrix metalloproteinase-7 (MMP-7), and hepatobiliary ultrasound; then, Kasai portoenterostomy (KPE) was performed promptly. The Roux-en-Y limb was adjusted intraoperatively to preserve the maximum length of the small intestine while closing the enterostomy. After the operation, the infant gradually adapted to enteral nutrition, his bilirubin level returned to normal, and his weight gradually caught up to the normal range. Although rare, BA should be suspected when MP is combined with IA and when the stool becomes paler in color in the enterostomy state.